2016
DOI: 10.1090/tran/6483
|View full text |Cite
|
Sign up to set email alerts
|

On the (co)homology of the poset of weighted partitions

Abstract: We consider the poset of weighted partitions Π w n , introduced by Dotsenko and Khoroshkin in their study of a certain pair of dual operads. The maximal intervals of Π w n provide a generalization of the lattice Π n of partitions, which we show possesses many of the well-known properties of Π n . In particular, we prove these intervals are EL-shellable, we show that the Möbius invariant of each maximal interval is given up to sign by the number of rooted trees on node set {1, 2, . . . , n} having a fixed numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…The In [22] the authors found a nice EL-labeling of Π w n ∪ {1} that generalized a classical EL-labeling of Π n due to Björner and Stanley (see [5]). An EL-labeling of a poset (defined in Section 3.2) is a labeling of the edges of the Hasse diagram of the poset that satisfies certain requirements.…”
Section: Doubly Bracketed Lie Algebramentioning
confidence: 80%
See 4 more Smart Citations
“…The In [22] the authors found a nice EL-labeling of Π w n ∪ {1} that generalized a classical EL-labeling of Π n due to Björner and Stanley (see [5]). An EL-labeling of a poset (defined in Section 3.2) is a labeling of the edges of the Hasse diagram of the poset that satisfies certain requirements.…”
Section: Doubly Bracketed Lie Algebramentioning
confidence: 80%
“…The symmetric group acts naturally on each Lie 2 (n, i) and on each open interval (0, [n] i ). In [22] González D'León and Wachs give an explicit S n -module isomorphism which establishes 3) and the isomorphism reduces to the one in [41]. In [22] bases for H n−3 ((0, [n] i )) and for Lie 2 (n, i) are constructed generalizing the classical Lyndon tree basis and the comb basis for H n−3 (Π n ) and Lie(n).…”
Section: Doubly Bracketed Lie Algebramentioning
confidence: 99%
See 3 more Smart Citations